2018
DOI: 10.1038/s41598-018-25191-4
|View full text |Cite
|
Sign up to set email alerts
|

EAAC1 gene deletion reduces adult hippocampal neurogenesis after transient cerebral ischemia

Abstract: Several studies have demonstrated that excitatory amino acid carrier-1 (EAAC1) gene deletion exacerbates hippocampal and cortical neuronal death after ischemia. However, presently there are no studies investigating the role of EAAC1 in hippocampal neurogenesis. In this study, we tested the hypothesis that reduced cysteine transport into neurons by EAAC1 knockout negatively affects adult hippocampal neurogenesis under physiological or pathological states. This study used young mice (aged 3–5 months) and aged mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Nevertheless, a study showed that cystine transport by cystine/glutamate antiporter (xCT) is not essential for novel proliferation in the DG, which illuminates the importance of EAAC1 as the main cysteine importer of cysteine in hippocampal regional mitosis. Our previous study showed that EAAC1 is important for the survival of newborn neurons in the adult hippocampus under physiological and ischemic conditions [46]. We found that there are no differences in cell proliferation and neuronal differentiation in both young and aged EAAC1 −/− mice under ischemia-free conditions compared to the age-matched WT mice.…”
Section: Reperfusion State and Neurogenesis Regarding Oxidationmentioning
confidence: 51%
See 3 more Smart Citations
“…Nevertheless, a study showed that cystine transport by cystine/glutamate antiporter (xCT) is not essential for novel proliferation in the DG, which illuminates the importance of EAAC1 as the main cysteine importer of cysteine in hippocampal regional mitosis. Our previous study showed that EAAC1 is important for the survival of newborn neurons in the adult hippocampus under physiological and ischemic conditions [46]. We found that there are no differences in cell proliferation and neuronal differentiation in both young and aged EAAC1 −/− mice under ischemia-free conditions compared to the age-matched WT mice.…”
Section: Reperfusion State and Neurogenesis Regarding Oxidationmentioning
confidence: 51%
“…Neurons that are differentiating can be detected by doublecortin (DCX), proopiomelanocortin (POMC), or neuronal nuclei (NeuN) antibodies. It has been reported that newly generated neurons in the dentate gyrus and striatum are GABAergic interneurons, with the former requiring two maturation steps and the latter needing only one [36,43,45,46]. The markers used to track down cellular mitosis in the rodent DG are as follows: Type I cells are marked by GFAP+Hes5+ or Nestin+Sox1+Sox2+BLBP (brain lipid-binding protein)+; Type II cells are marked by Nestine+Sox1+Sox2+BLBP+ or Mash1+ or Prox1+NeuroD+; type III cells are marked by NeuroD1+DCX+; and mature neurons are marked by NeuN+ [44].…”
Section: Neurogenesis: a General Understandingmentioning
confidence: 99%
See 2 more Smart Citations
“…41 Additionally, concentrations of hydrogen peroxide and superoxide play a role in the choice to either enter or exit the cell cycle. 42 In support of these observations, we previously demonstrated that newly generated neurons are exposed to oxidative stress at specific developmental timepoints, potentially explaining effects on hippocampal neurogenesis 43 observed in these animals. To test this, we used ZN which is zinc chloride mixed with NAC in 1:2 M ratio to increase brain zinc and cysteine levels.…”
Section: Zn Treatment Increases Igf-1 Expression and Erk/creb Activmentioning
confidence: 65%